Analysis of reasons and risk factors for non-completion of radiotherapy courses in patients with tumors - Chen, Meihua; Li, Kexin; Gao, Xuan; Ye, Xia; Ju, Yongjian (Frontiers in Oncology, 2025)
PurposeNon-completion of radiotherapy courses (NCRC) may happen in patients undergoing intensity-modulated radiotherapy (IMRT). Analyzing the reasons and risk factors for NCRC can lead to possible targeted measures to reduce the incidence rate. This six-year retrospective study will present a cohort analysis of NCRC from a single center.MethodsData from patients treated with IMRT between January 2018 and December 2023 were collected for analysis. The collected characteristics included age, gender, residential area, body mass index (BMI), tumor clinical stage, tumor type, tumor location, therapeutic intent, number of fractions, insurance status, treatment completion status, and reasons for NCRC. The radiotherapy process rigorously followed Chinese basic guidelines of quality control for radiotherapy. NCRC was defined as the failure to complete the course after starting the radiotherapy. Patients were categorized into the completion group (CG) and the non-completion group (NCG). Comprehensive analyses included six-year overall NCRC rate and annual trends, inter-group (CG vs. NCG) characteristic disparities, the reasons and risk factors for NCRC.ResultsAmong total collected 2,112 IMRT patients, the overall rate of NCRC was 5.68% (n=120), with annual values ranging 4.15–6.69% (p=0.718). The patient-driven reasons for NCRC encompassed: perceiving the final several fractions as non-essential (n=8, 6.67%); perceived insufficient therapeutic efficacy (n=34, 28.33%); financial constraints (n=3, 2.5%). The clinician-driven reasons for NCRC included: severe radiation-induced toxicities (n=39, 32.5%); disease progression (n=30, 25%); death(n=6, 5%). Significant inter-group (CG vs. NCG) differences (p<0.05) were observed in age, gender, body mass index (BMI), therapeutic intent, tumor clinical stage, tumor location, and number of fractions; however significant differences were not observed in the residential area and insurance status. Multivariate analysis revealed that the age, BMI, therapeutic intent, and tumor clinical stage were independent risk factors for NCRC (p<0.05).ConclusionRigorous adherence to the basic guidelines of radiotherapy quality control helped maintain a stable NCRC rate (ranging 4.15%–6.69%). While 62.5% of NCRC cases were attributable to unpredictable radiation-induced toxicities, disease progression or death, the remaining 37.5% (35% due to insufficient awareness of radiotherapy and 2.5% to financial constraints) were potentially preventable. These findings underscore the need for implementing risk-stratified interventions to address modifiable barriers and reduce NCRC rates, particularly in high-risk subgroups characterized by advanced age, lower BMI, later clinical tumor stage, and palliative radiotherapy intent.